KEBERHASILAN IMPLEMENTASI SISTEM INFORMASI AKUNTANSI DALAM PERSPEKTIF KOMITMEN ORGANISASIONAL DAN PENGETAHUAN MANAJER - Mochammad Ridwan; Budi Septiawan; Sasa S Suratman (JRAK, 2019)
This study aims to determine the influence of organizational commitment and knowledge of accounting managers on the successful implementation of accounting information systems either simultaneously or partially. It was conducted at SOE in West Java. The research method used were descriptive and verification method. The number of samples were 33 companies, with a simple random sampling technique. The type of data is primary data obtained through a questionnaire distributed to the accounting department manager. The analysis used is multiple linier regression analysis. The results indicated that the level of organizational commitment and the successful implementation of accounting information systems are in the high category, the knowledge of accounting managers is in the very high category. Either simultaneously or partially organizational commitment and knowledge of accounting managers have a positive and significant effect on the successful implementation of accounting information systems at SOE in West Java. The greatest influence is the knowledge of accounting managers.